Development and Quality Assessment of Functional Chicken Star - Nayak, N.K.; Pathak, V.; Bharti , S.K.; Goswami , M. (Journal of Meat Science, 2015)
The objective of this study was to evaluate the effect of carrageenan at different levels as fat replacer to develop functional chicken star. The physico-chemical, proximate and sensory quality of chicken meat star was evaluated. Results indicated that the pH, cooking yield, emulsion stability and moisture content was significantly (p<0.05) higher in carrageenan added chicken star. The fat content and cholesterol contents were significantly (p<0.05) reduced in treated chicken star. However, protein and ash content differed non-significantly (p>0.05) in between treatments and control. The fat and moisture retention capacity of the functional chicken star were also improved significantly (p<0.05) with the incorporation of carrageenan. The mean scores for appearance and colour as well as flavor were non-significantly (p>0.05) higher in functional chicken star. Texture and juiciness were comparable in T 2 (emulsion with 5% vegetable oil + 0.6% hydrated carrageenan) functional chicken star and full fat chicken star. However, the mean value of overall acceptability score increased significantly (p<0.05) in developed product. On the basis of physicochemical properties it may be concluded that the carrageenan may be best suitable fat replacer to develop functional chicken star without affecting the sensory attributes.